Immunosuppression - Role in Health and Diseases 2012
DOI: 10.5772/29549
|View full text |Cite
|
Sign up to set email alerts
|

Immunodepression and Immunosuppression During Aging

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 104 publications
1
24
0
Order By: Relevance
“…FVB and B6 mice were chosen, because these strains belong to different phylogenetic clusters [45, 46] and display dissimilar T-Cell Receptor (TCR) repertoires as explained by chromosomal deletion of six Beta chain Variable region (BV) TCR families in FVB [47]. B6 and FVB mice differ in their lymphocyte and T cell compositions [48] and numbers in the various populations at steady-state [30]. Moreover, FVB mice display accelerated thymic involution and aging of VB repertoire as compared to B6 mice [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FVB and B6 mice were chosen, because these strains belong to different phylogenetic clusters [45, 46] and display dissimilar T-Cell Receptor (TCR) repertoires as explained by chromosomal deletion of six Beta chain Variable region (BV) TCR families in FVB [47]. B6 and FVB mice differ in their lymphocyte and T cell compositions [48] and numbers in the various populations at steady-state [30]. Moreover, FVB mice display accelerated thymic involution and aging of VB repertoire as compared to B6 mice [30].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, no clear consensus has been reached concerning the influence of genetics and age on T cell dynamics. We have previously observed that both the genetic background and aging affect T cell dynamics and repertoires [30]. Indeed, C57BL/6 and FVB mice differ in their T cell composition at steady state but also in their kinetics of T cell reconstitution after a transient immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunization conditions and antigen doses are expected to lead to immune, tolerant, or hyper-reactivity conditions (12). Yet, in vivo perturbation and shrinking of the network through aging or transient depletion of dividing lymphocytes affect repertoire composition (16), tolerance (17), and memory maintenance leading to immunological amnesia (18). Therapies for regulation of inflammation by ‘T cell vaccination’ or homuncular self-antigen immunization, by inducing a regulatory anti-idiotypic network, are thus proposed to cure auto-immune diseases in the long run rather than global immunosuppression (19).…”
mentioning
confidence: 99%
“…Therapies for regulation of inflammation by ‘T cell vaccination’ or homuncular self-antigen immunization, by inducing a regulatory anti-idiotypic network, are thus proposed to cure auto-immune diseases in the long run rather than global immunosuppression (19). Otherwise, low-dose IL-2 administration to stimulate autoreactive Treg to control effector lymphocyte expansion during aging (16) or to prevent autoimmune diseases is promising.…”
mentioning
confidence: 99%